Math, asked by khushi9125, 1 year ago

ques 25 ii plz solve it

Attachments:

Answers

Answered by ravisanplapcjwiv
1
I hope you will be able to understand
Attachments:
Answered by Shubhendu8898
1

 Given, \\ \\  \sec^{4}\theta - \tan^{4} \theta \\ \\ = (\sec^{2}\theta - \tan^{2}\theta)*(\sec^{2}\theta + \tan^{2}\theta) \\ \\ = 1* (\sec^{2}\theta + \tan^{2}\theta) \\ \\  = 1 + \tan^{2}\theta + \tan^{2}\theta \\ \\ = 1 + 2\tan^{2}\theta \\ \\ = R.H.S. \\ \\ \textbf{proved}<br /><br />\textit{ Identities used:-} <br /><br />1. (a^{2}  - b^{2}) = (a+b)(a-b) \\ \\<br />2. \sec^{2}\theta - \tan^{2}theta = 1<br /><br />

Similar questions